ANALISIS NILAI TAMBAH HASIL BUDIDAYA SAWI HIDROPONIK SISTEM WICK PADA MASA PANDEMI COVID 19 - samudi; Ratna Dewi Mulyningtiyas; Lina Saptaria (JURNAL ILMIAH AGRINECA, 2021)
Cultivating mustard greens with a hydroponic system was a profitable business opportunity and is very suitable to run during the Covid 19 pandemic. Added value has an important role in the hydroponic farmer's decision-making process regarding whether or not to run a mustard vegetable cultivation business opportunity. This study aims to determine the added value of family economic results from the entrepreneurial results of hydroponic mustard cultivation using the wick system during the Covid 19 pandemic. This type of research is a quantitative descriptive study. The quantitative analysis carried out includes analysis of costs, revenues, profits, profitability, analysis of business efficiency, and added value. Data analysis to calculate the added value using the Hayami method. Based on the results of the analysis of the value-added analysis of hydroponic mustard cultivation using the wick system during the covid 19 pandemic, it was concluded that the total cost was Rp. 404.400,- total receipt of Rp. 720,000,-; profit value Rp. 315,600,- while the added value from hydroponic mustard cultivation activities, the added value obtained from hydroponic vegetables is Rp. 68.000/kg While the ratio of the added value of hydroponic mustard is 38.20% meaning 38.20 percent of the output value is the added value obtained from hydroponic vegetable cultivation.